2015
DOI: 10.1146/annurev-nutr-071813-105330
|View full text |Cite
|
Sign up to set email alerts
|

The Ontogeny of Brown Adipose Tissue

Abstract: There are three different types of adipose tissue (AT)-brown, white, and beige-that differ with stage of development, species, and anatomical location. Of these, brown AT (BAT) is the least abundant but has the greatest potential impact on energy balance. BAT is capable of rapidly producing large amounts of heat through activation of the unique uncoupling protein 1 (UCP1) located within the inner mitochondrial membrane. White AT is an endocrine organ and site of lipid storage, whereas beige AT is primarily whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 146 publications
0
102
0
Order By: Relevance
“…It has been also found in neonates of large mammalian species and more recently, in adults (Lee et al, 2013). As observed in human, BAT depots in sheep are mainly found in the supraclavicular/ neck region and in the pericardial and perirenal regions (Symonds et al, 2015). Perirenal, pericardial and peritoneal adipose tissues in calf neonates have been essentially recognized as brown (Casteilla et al, 1989;Martin et al, 1999;Smith et al, 2004), but recent studies revealed that fetal bovine perirenal adipose tissue may have much more in common with WAT than with BAT (Taga et al, 2012a and.…”
Section: Overview Of Structure Location and Functions Of Adipose Tismentioning
confidence: 67%
“…It has been also found in neonates of large mammalian species and more recently, in adults (Lee et al, 2013). As observed in human, BAT depots in sheep are mainly found in the supraclavicular/ neck region and in the pericardial and perirenal regions (Symonds et al, 2015). Perirenal, pericardial and peritoneal adipose tissues in calf neonates have been essentially recognized as brown (Casteilla et al, 1989;Martin et al, 1999;Smith et al, 2004), but recent studies revealed that fetal bovine perirenal adipose tissue may have much more in common with WAT than with BAT (Taga et al, 2012a and.…”
Section: Overview Of Structure Location and Functions Of Adipose Tismentioning
confidence: 67%
“…WAT is endocrine in nature and lipid storage site and is implicated as an endocrine organ that secretes hormones and different molecules as growth factors, complement factors, enzymes, and pro-and anti-inflammatory cytokines among others [2]; while BeAT is primarily white, it has some cells that have UCP-I. BrAT appears first in the fetus mid-gestation and is lost during the maturation of childhood, adolescence, and mature age [4].…”
Section: Morphology and Physiology Of Adipose Tissuementioning
confidence: 99%
“…Non-myelinated axons terminate in fat cells, providing for a direct sympathetic regulation, and the vascularity is ample with numerous capillaries coursing between the adipocytes [4]. Brown adipose cells have numerous mitochondria that participate in heat production through UCP-1 protein.…”
Section: Brown Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…BAT is a thermogenic organ located mainly in the supraclavicular regions and in much smaller amounts 5 in other locations such surrounding the kidneys and heart. Most abundant at birth 6 , BAT is responsible for nonshivering thermogenesis and the maintenance of thermal homeostasis. This is achieved through the uncoupling of oxidative metabolism from ATP production via mitochondrial uncoupling protein 1 which dissipates chemical energy as heat 7 .…”
Section: Commentarymentioning
confidence: 99%